Contenção física de serpentes: técnicas e precauções - Passos, Rodrigo Rabello de Figueiredo Carvalho e Ferreira (2009)
Reptiles are animals that attract by their diversity and among them, the snakes deserve emphasis on use commercially like pet s and biological immune production. Considering the difficulties and the risk of management, is described methods off physic contention in snakes, including equipments and cautions. Was used hook, manual contention, barrows contention, Lutz s tie, bag of fabric and fabric, contention and transport box and bedding foam in 130 animals for 4 families, Boidae, Viperidae, Elapidae and Colubridae. The snakes physics contention techniques described in these opportunity was effective, provided that the conditions imposed by each state.